Dietary Intake of Purple Corn Extract Reduces Fat Body Content and Improves Antioxidant Capacity and n‐3 Polyunsaturated Fatty Acid Profile in Plasma of Rainbow Trout, Oncorhynchus mykiss. Issue 4 (August 2015) - Villasante, Alejandro; Patro, Biswamitra; Chew, Boon; Becerra, Michael; Wacyk, Jurij; Overturf, Ken; Powell, Madison S.; Hardy, Ronald W.
Abstract A study was conducted to determine the benefits of the intake of purple corn extract (PCE), a natural source of anthocyanins, in rainbow trout, Oncorhynchus mykiss. A control or test diet supplemented with 5% PCE was fed to triplicate tanks with 25 fish each for 8 wk. The concentrations of three anthocyanins, cyanidin‐3‐glucoside, pelargonidin‐3‐glucoside, and peonidin‐3‐glucoside, were measured in PCE. The chemical composition and fatty acid profiles of fish, as well as the fatty acid profiles in plasma, liver, and muscle were determined. The total antioxidant capacity (TAC) and the concentration of oxidative damage biomarkers, for example, protein carbonyls, 8‐hydroxydeoxyguanosine, and thiobarbituric acid reactive substances (TBARS), were determined in plasma. Transcription of two antioxidant enzymes, glutathione peroxidase 1 (gpx1) and superoxide dismutase 1 (sod1), was measured in erythrocytes. Significant lower adiposity and significant higher percentage of total n‐3 and total n‐6 polyunsaturated fatty acids (PUFA) in the body of fish fed the test diet were detected. Significant higher plasma percentage of total n‐3 PUFA, significant higher plasma TAC, and significant higher expression of gpx1 in erythrocytes of fish fed the test diet were measured. Overall, our results suggest potential protection against in vivo lipid peroxidation in fish fed the PCE supplemented diet. This is especially true due to detection of an enhanced antioxidant protection in plasma and erythrocytes in fish, the reduced adiposity and greater proportion of total n‐3 and n‐6 PUFA in the fish body, as well as a tendency toward lower TBARS plasma concentration in fish fed the test diet when compared to the control group.